1996
DOI: 10.1021/ef9501455
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodesulfurization of Refractory Sulfur Species. 2. Selective Hydrodesulfurization of 4,6-Dimethyldibenzothiophene in the Dominant Presence of Naphthalene over Ternary Sulfides Catalyst

Abstract: The catalytic activities of sulfided Ru−CoMo/Al2O3 were examined for the desulfurization of 4,6-dimethyldibenzothiophene (4,6-DMDBT) in decane and decane with naphthalene to find selective catalysts which desulfurize 4,6-DMDBT in the presence of naphthalene through preferential hydrogenation of its phenyl ring. Addition of Ru to CoMo catalyst exhibited an excellent activity for HDS of 4,6-DMDBT and suffered less inhibition by coexisting naphthalene, whereas significant retardation was observed over NiMo/Al2O3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…Naphthalene Inhibition. A variety of polyaromatic compounds present in the diesel oil adsorb completely with sulfur species on the same catalyst surface. It was found in the present study that the increasing concentration of naphthalene in the feedstock increased the ratio of [HYD]/[DDS] slightly at a 50% conversion level, although naphthalene reduced both the rates. It should be remembered that the [HYD/DDS] ratio varies with the conversion level.…”
Section: Discussionmentioning
confidence: 49%
“…Naphthalene Inhibition. A variety of polyaromatic compounds present in the diesel oil adsorb completely with sulfur species on the same catalyst surface. It was found in the present study that the increasing concentration of naphthalene in the feedstock increased the ratio of [HYD]/[DDS] slightly at a 50% conversion level, although naphthalene reduced both the rates. It should be remembered that the [HYD/DDS] ratio varies with the conversion level.…”
Section: Discussionmentioning
confidence: 49%
“…There are two possible approaches for the efficient desulfurization of 4,6-DMDBT: (1) the selective hydrogenation of 4,6-DMDBT in the dominant aromatic partners and (2) hydrodesulfurization (HDS) reaction after the migration of substituted methyl groups in 4,6-DMDBT. The present authors have reported that blends of Ru/Al 2 O 3 and CoMo/Al 2 O 3 catalysts or Ru-CoMo/Al 2 O 3 catalyst showed higher hydrogenation selectivity for 4,6-DMDBT in a high concentration of naphthalene than conventional CoMo/Al 2 O 3 and NiMo/Al 2 O 3 . However, no isomerization reaction was found over the conventional catalysts. , …”
Section: Introductionmentioning
confidence: 64%
“…Girgis et al reported that HDS reactivity of sulfur species was hindered by sulfur-, oxygen-, and nitrogen-containing species. In an earlier study, we reported that the HDS reaction of 4,6-DMDBT was greatly decreased by hydrogen sulfide, which was added or produced from coexisting benzothiophene (BT) . However, additive dibenzothiophene (DBT) did not affect the reactivity of 4,6-DMDBT.…”
Section: Resultsmentioning
confidence: 99%